2021
DOI: 10.1101/2021.02.09.430114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell ATAC and RNA sequencing reveal pre-existing and persistent subpopulations of cells associated with relapse of prostate cancer

Abstract: Prostate cancer is profoundly heterogeneous and patients would benefit from methods that stratify clinically indolent from more aggressive forms of the disease. We employed single-cell assay for transposase-accessible chromatin (ATAC) and RNA sequencing in models of early treatment response and resistance to enzalutamide. In doing so, we identified pre-existing and treatment-persistent cell subpopulations that possess transcriptional stem-like features and regenerative potential when subjected to treatment. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Through spot deconvolution and prior cell marker genes, researchers can estimate the cell composition of spots and further divide the ST sections into several spatially different areas i.e., tumor area, tumor leading-edge area and paratumor area. Several pilot studies have shown ST-based pathological annotations displayed comparable or even higher accuracy than that from pathologists (38,82,110,112,123) (Table 2). Moreover, ST can distinguish cancer subtypes as well (108).…”
Section: Clinical Application Of St Diagnosismentioning
confidence: 97%
See 2 more Smart Citations
“…Through spot deconvolution and prior cell marker genes, researchers can estimate the cell composition of spots and further divide the ST sections into several spatially different areas i.e., tumor area, tumor leading-edge area and paratumor area. Several pilot studies have shown ST-based pathological annotations displayed comparable or even higher accuracy than that from pathologists (38,82,110,112,123) (Table 2). Moreover, ST can distinguish cancer subtypes as well (108).…”
Section: Clinical Application Of St Diagnosismentioning
confidence: 97%
“…It is very important to predict the response of cancer patients for specific cancer therapy clinically. However, it is quite difficult due to complex tumor heterogeneity (2,123). ScRNA-seq has revealed specific cell components could influence treatment response in diverse cancers (127).…”
Section: Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Microfluidics‐based single‐cell sequencing methods are reliable tools to elucidate tumor growth, development, metastasis, and drug resistance 90 . So far, a variety of cancers, such as lung cancer, 91 ] [ 92 breast cancer, 93 ] [ 94 ] [ 95 prostate cancer, 96 ] [ 97 ] [ 98 ] [ 99 , liver cancer 100 , epithelial ovarian cancer (EOC) 101 , and so on have been explored at the single‐cell level, providing critical insight for cancer monitoring, diagnosis, and treatment.…”
Section: Biological Applications and Clinical Practicementioning
confidence: 99%
“…An in-depth analysis of scATAC-seq data can reveal distinct cell populations, roles of key transcription factor, gene regulatory programs underlying cell heterogeneity, and trajectories of cell lineage differentiation (Baek and Lee, 2020;Granja et al, 2021). So far, scATAC-seq has been used for investigating epigenetic heterogeneity in complex tissues during normal development and diseases, such as an array of adult tissues (Cusanovich et al, 2018;Liu et al, 2019;Zhang K. et al, 2021;Chen et al, 2021;Fang et al, 2021), developing tissues and embryos (Preissl et al, 2018;Pijuan-Sala et al, 2020), immune cell development (Buenrostro et al, 2018;Satpathy et al, 2019), spermatogenesis (Wu et al, 2021), and tumor progression (LaFave et al, 2020;Taavitsainen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%